Drug-Associated Thrombotic Microangiopathies - Kreuter, Justin; Winters, Jeffrey L. (Seminars in Thrombosis and Hemostasis, 2012)
Thrombotic microangiopathy is a pathological process that results in thrombocytopenia, schistocytes, and organ ischemia. A wide variety of causes of thrombotic microangiopathy have been described, each associated with a different pathological stimulus and predisposition toward certain vascular territories. This review will summarize our understanding of key drugs that have been classically and newly associated with thrombotic microangiopathy as well as mention of treatment options focusing on the role of plasma exchange.
Keywords: drug; thrombotic microangiopathy; plasma exchange